2022
DOI: 10.1681/asn.2022020189
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of Escherichia-Shigella in Gut Is Associated with the Onset and Response to Immunosuppressive Therapy of IgA Nephropathy

Abstract: BackgroundGut dysbiosis is postulated to participate in the pathogenesis of IgA nephropathy (IgAN). However, the key bacterial taxa closely associated with IgAN onset and treatment response have not been identified.MethodsWe recruited 127 patients with IgAN who were treatment naive and 127 matched healthy controls (HCs) who were randomly divided into discovery and validation cohorts to investigate the characteristics of their gut microbiota and establish a bacterial diagnosis model for IgAN. A separate cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 55 publications
0
29
0
Order By: Relevance
“…Previous studies on the IgAN microbiome usually focused on oral or gut microbiota ( 12 , 14 18 ). Our study provided the first systematic survey of microbial diversity across four distinct niches of IgAN patients, revealing niche-specific patterns of microbial dysbiosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on the IgAN microbiome usually focused on oral or gut microbiota ( 12 , 14 18 ). Our study provided the first systematic survey of microbial diversity across four distinct niches of IgAN patients, revealing niche-specific patterns of microbial dysbiosis.…”
Section: Discussionmentioning
confidence: 99%
“…In tonsils, patients with IgAN had higher proportions of Rahnella , Ruminococcus_g2 , and Clostridium_g21 , according to one study of 21 patients and 23 controls in a Korean population ( 13 ). Many studies on the gut microbial composition in IgAN patients have suggested an increase in some pathogenic genera, such as Escherichia - Shigella ( 14 18 ) and Eggerthella ( 15 ), with a reduction in some beneficial bacteria, such as Bifidobacterium and Blautia spp. ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…The latest study showed that gut microbiome plays an essential role in onset of MN and can be used as a noninvasive diagnostic tool (Shang et al, 2022). Zhao et al reported that Escherichia‐Shigella , as the biggest contributor among seven operational taxa units, could optimally classify IgAN, but cannot distinguish between IgAN and IMN, which instead is associated with enrichment of shigellosis infection pathway in IgAN (Zhao, Bai, et al, 2022). In addition, Luan et al reported that Alloprevotella , Granulicatella , Prevotella , Streptococcus and Prevotella_7 in salivary samples showed a high relative abundance in IMN patients compared with healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…In the digesta-associated microbiota of the FW group, Escherichia-Shigella was significantly negatively related to il10, tgfβ1 , and il17F. Escherichia-shigella is considered as a pathogen to humans and animals ( Falkow et al, 1963 ; Zhao et al, 2022 ). Its pathogenic function may explain its negative interaction with anti-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%